Influence of Different Energy Supply Methods on Performance of Ablative Pulsed Plasma Thrusters - Zhang, Rui; Xi, Wenxiong; Huang, Qiang (Frontiers in Energy Research, 2021)
For a certain configuration of ablative pulsed plasma thruster, changing the initial energy is an effective way to optimize the performance of the thruster. Different energy supply methods will not only affect the macro discharge characteristics and system performance of the thruster, but also affect the micro characteristics of the plasma in the discharge channel, the equivalent parameters of the discharge circuit, energy conversion efficiency and so on. In this study, the discharge characteristics, ablation characteristics and plasma motion characteristics of the thruster under different energy supply methods are analyzed experimentally and theoretically. The results show that using the method which includes increasing capacitance to heighten the initial energy of system under the same voltage, using a low-voltage, large-capacitor power supply method under the same initial energy, can effectively increase the impulse generated by Lorentz force and its proportion in the impulse bit. Moreover, the proportion of the ablative propellant effectively ionized and accelerated by Lorentz force increases. Therefore, the thruster has higher specific impulse and efficiency.